Temperate Forest Floors: Ecosystem Hubs in Transition? - Friederike Lang; Jörg Prietzel; Frank Hagedorn; Klaus Kaiser; Stefanie Schulz; Mathias Mayer; Lars Vesterdal; Jürgen Bauhus; Maï Bergmann; Sebastian Bibinger; Martin I. Bidartondo; Jingxuan Olivia Chen; et al. (Global Change Biology, 2026)
The forest floor (FF) plays a key role in carbon, nutrient, and water cycling. It is the biologically most active compartment of forest soils, highly responsive to environmental conditions. Yet, its response to current changes in environmental conditions and forest management is understudied. Temperate forests are among the best studied ecosystems globally, providing the necessary ecological and biogeochemical background information to assess FF changes. Here, we focus on identifying existing knowledge and gaps in our understanding of the functioning of the FF. Interactions between FF biota and abiotic FF components show multifactorial dependencies with environmental conditions and drive FF turnover. Vice versa, the turnover of FF regulates carbon, nutrient, and water cycling. With slow litter decomposition and limited bioturbation, organic matter accumulates, nutrients cycle tightly within the FF, and water passes through this layer partly along preferential pathways. With rapid litter decomposition and intense bioturbation, FF accumulation is little, the mineral soil is the main nexus for plant nutrient uptake and organic matter transformation, and water infiltrates the mineral soil more homogeneously. The interconnectedness with the adjacent ecosystem compartments is a crucial feature of the FF, feeding back to its functioning and making it a central hub of forest processes. The FF morphology reflects these processes and therefore has untapped potential as an indicator of soil and ecosystem health. Under forest change, the FF might lose its functionality, with negative impacts on nutrient provision, water storage, and carbon sequestration. Consequences for forest growth could be strong and even detrimental. Hence, improved knowledge of FF characteristics and their linkages to mineral soils and aboveground ecosystem compartments is crucial for assessing forest resilience to progressing environmental changes.

EnsembleAge: enhancing epigenetic age assessment with a multi-clock framework - Amin Haghani; Ake T. Lu; Qi Yan; Juan Carlos Izpisua Belmonte; Pradeep Reddy; Victor Cheng; X. William Yang; Nan Wang; Khyobeni Mozhui; Kevin Murach; Alejandro Ocampo; Robert W. Williams; et al. (GeroScience, 2025)
Several widely used epigenetic clocks have been developed for mice and other species, but a persistent challenge remains: different mouse clocks often yield inconsistent results. To address this limitation in robustness, we present EnsembleAge, a suite of ensemble-based epigenetic clocks. Leveraging data from over 200 perturbation experiments across multiple tissues, EnsembleAge integrates predictions from multiple penalized models. Empirical evaluations demonstrate that EnsembleAge outperforms existing clocks in detecting both pro-aging and rejuvenating interventions. Furthermore, we introduce EnsembleAge HumanMouse, an extension that enables cross-species analyses, facilitating translational research between mouse models and human studies. Together, these advances underscore the potential of EnsembleAge as a robust tool for identifying and validating interventions that modulate biological aging.

Boosting working memory in the elderly: driving prefrontal theta–gamma coupling via repeated neuromodulation - Lukas Diedrich; Hannah I. Kolhoff; Clara Bergmann; Mathias Bähr; Andrea Antal (GeroScience, 2024)
The escalating global burden of age-related neurodegenerative diseases and associated healthcare costs necessitates innovative interventions to stabilize or enhance cognitive functions. Deficits in working memory (WM) are linked to alterations in prefrontal theta–gamma cross-frequency coupling. Low-intensity transcranial alternating current stimulation (tACS) has emerged as a non-invasive, low-cost approach capable of modulating ongoing oscillations in targeted brain areas through entrainment. This study investigates the impact of multi-session peak-coupled theta–gamma cross-frequency tACS administered to the dorsolateral prefrontal cortex (DLPFC) on WM performance in older adults. In a randomized, sham-controlled, triple-blinded design, 77 participants underwent 16 stimulation sessions over six weeks while performing n -back tasks. Signal detection measures revealed increased 2-back sensitivity and robust modulations of response bias, indicating improved WM and decision-making adaptations, respectively. No effects were observed in the 1-back condition, emphasizing dependencies on cognitive load. Repeated tACS reinforces behavioral changes, indicated by increasing effect sizes. This study supports prior research correlating prefrontal theta–gamma coupling with WM processes and provides unique insights into the neurocognitive benefits of repeated tACS intervention. The well-tolerated and highly effective multi-session tACS intervention among the elderly underscores its therapeutic potential in vulnerable populations.

An Integrated System for 3D Hip Joint Reconstruction from 2D X-rays: A Preliminary Validation Study - Steffen Schumann; Li Liu; Moritz Tannast; Mathias Bergmann; Lutz-P. Nolte; Guoyan Zheng (Annals of Biomedical Engineering, 2013)

Differential appearance of dynamin in constitutive and regulated exo-endocytosis: a single-cell multiplex RT-PCR study - Detlev Grabs; Mathias Bergmann (Cell and Tissue Research, 2005)

Expression of synaptophysin in sprouting neurons after entorhinal lesion in the rat - Mathias Bergmann; Anke Post; Isabell Rittel; Ingo Bechmann; R. Nitsch (Experimental Brain Research, 1997)